2017
DOI: 10.1080/09513590.2017.1323859
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis in 46 women with vulvovaginal atrophy treated with ospemifene for 12 weeks: improvement in overactive bladder symptoms

Abstract: Ospemifene is an effective potential therapy for postmenopausal women with VVA improving OAB symptoms and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The findings of the present study support the effectiveness and safety of purified bovine colostrum (Monurelle Biogel) in improving (VVA), sexual function, urinary symptoms, and QoL in postmenopausal patients with GSM. Large cohort studies have reported the prevalence of vaginal dryness in postmenopausal women of 27% to 55% and a prevalence of dyspareunia of 32% to 41%, but with early identification, treatment can improve these symptoms and reverse the physical changes . Local estrogen therapy is the first line recommended treatment, more effective than systemic therapy, to alleviate subjective symptoms of atrophy in healthy postmenopausal women without VMS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the present study support the effectiveness and safety of purified bovine colostrum (Monurelle Biogel) in improving (VVA), sexual function, urinary symptoms, and QoL in postmenopausal patients with GSM. Large cohort studies have reported the prevalence of vaginal dryness in postmenopausal women of 27% to 55% and a prevalence of dyspareunia of 32% to 41%, but with early identification, treatment can improve these symptoms and reverse the physical changes . Local estrogen therapy is the first line recommended treatment, more effective than systemic therapy, to alleviate subjective symptoms of atrophy in healthy postmenopausal women without VMS .…”
Section: Discussionmentioning
confidence: 99%
“…Menopause is a physiological condition associated with estrogen deficiency, inducing vaginal and vulvar dryness, commonly known as vulvovaginal atrophy (VVA) . Vaginal dryness reduces lubrication during sexual intercourse, resulting in pain and other female sexual dysfunctions (FSD), and may interfere with simple activities such as walking or exercising, compromising quality of life (QoL) . Estrogen deficiency may also be associated with lower urinary tract symptoms (LUTS) such as dysuria, urethral discomfort, overactive bladder (OAB) symptoms, and stress or urge urinary incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…There were also significant improvements in OAB questionnaire scores. A retrospective review of 46 women using ospemifene for GSM found a significant improvement in frequency, nocturia, urgency, and urgency incontinence 30 .…”
Section: Genitourinary Syndrome Of Menopause Treatment For Oabmentioning
confidence: 99%
“…Another study showed that 6 months of ospemifene significantly reduced recurrent UTIs in 39 women with GSM; these women also had improvements in sexual function with ospemifene [80]. A retrospective analysis found that 12 weeks of ospemifene significantly reduced urgency and other overactive bladder symptoms in postmenopausal women with VVA (n = 46) [81]. Further study of ospemifene as a potential treatment for the urinary component of GSM is warranted.…”
Section: Expert Opinionmentioning
confidence: 99%